Are We All Speaking the Same Language? Exploring Language Interactions in the Homes of Young Latino DLLs Living in the U.S. Issue 8 (16th November 2020) - López, Lisa M.; Komaroff, Eugene; Scheffner Hammer, Carol; Rodriguez, Barbara; Scarpino, Shelley; Bitetti, Dana; Goldstein, Brian
ABSTRACT: Research Findings : The Latino population within the U.S. is heterogeneous with diversity in education level, country of origin, and English language fluency. Latino children often enter school with limited English language skills. In the current study, we surveyed 448 Latino families of Cuban, Mexican, and Puerto Rican descent regarding their home language use providing an in-depth look at the language interactions within Latino families residing in the U.S. Adults were matched on the language used with each other and with the target child. Six main findings are reported: (1) Mother–father language matched in 94% of the homes. Frequency distributions and cross-tab analysis identified Spanish as the primary language spoken in 56% of the homes, (2) Children and parents matched in language spoken in less than 21% of the homes, (3) Fathers play an important role in language use at home, (4) Approximately half of the mothers report no English fluency, (5) Latino children prefer to speak English at home, and (6) Maternal English fluency is related to overall language use. Practice or Policy : Early Childhood professionals should carefully structure language experiences in the classroom to aid the language acquisition of DLLs while promoting bilingualism. In addition, programs must take into consideration language spoken at home when establishing communication with the families.